Differences Between Passing Techniques and Peer Tutoring Method in Volleyball Games for students OF Tamansari 1 Elementary School, Dringu District, Probolinggo Regency - Cahyono, Agus; Sudarsono, Sudarsono (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The results of this study aimed to determine the differences in the underhand passing technique with the peer tutor method in volleyball games for students of MI Al Fattah, Malang City. The research method was a quasi-experimental method. The sampling technique was simple random sampling. The sample was 20 students of class 5 A as the experimental class and 20 students of class 5 B as the control class. The data collection technique used tests and non-tests. The instruments were tests and non-test instruments in the form of questionnaires. The data obtained were analyzed using the prerequisite test of normality and homogeneity tests. The results of the t-test that had been carried out with the SPSS program, obtained that the t-count value was greater than the t-table value, meaning that there was a significant difference in the underhand passing technique with the peer tutor method in volleyball games for students of MI Al Fattah, Malang City.